(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
The 21st century territorial competition has become a contest between economic realities able to compete locally and globally. The proposal for innovative products and services seems to be the right way for companies who want to enter in this context as protagonists. This paper analyzes the data about a region of southern Italy, Apulia, trying to figure out what could be the importance of technological innovation on the performance of individual companies; the causes of the lack of innovation in Puglia and possible strategies to exit by this stage of impasse will be investigated.